Respuesta :
[tex]3\sqrt{6} = \sqrt{9}*\sqrt{6} = \sqrt{9*6} = \sqrt{54}[/tex]
The rule I'm using is
[tex]\sqrt{x}*\sqrt{y} = \sqrt{x*y}[/tex]
note how I rewrote "3" into the square root of 9, so that everything would have a square root over it, and that allows me to use that rule above.
[tex]\sqrt{54}[/tex] equivalent to the expression [tex]3\sqrt{6}[/tex].
What is expression?
Expressions in math are mathematical statements that have a minimum of two terms containing numbers or variables, or both, connected by an operator in between.
Given expression
[tex]3\sqrt{6}[/tex]
We have the property [tex]\sqrt{x}[/tex] × [tex]\sqrt{y}[/tex] = [tex]\sqrt{x.(y)}[/tex]
[tex]3\sqrt{6}[/tex]
= [tex]\sqrt{9}[/tex] × [tex]\sqrt{6}[/tex]
= [tex]\sqrt{9.(6)}[/tex]
= [tex]\sqrt{54}[/tex]
[tex]\sqrt{54}[/tex] equivalent to the expression [tex]3\sqrt{6}[/tex].
Find out more information about expression here
https://brainly.com/question/14961928
#SPJ3